Analisa Segmentasi Penjualan Rumah Di Batam - Muhammad Donal Mon; Andi Andi (ConCEPt - Conference on Community Engagement Project, 2021)
Internship taken by researcher has started from 30 May 2019 until 30 October 2019. The results shows that performance appraisal play an important role toward company’s decision making process. Method used in this internship include interviews, field observations, designing sytem and implementating the Website Online Sytem through company. The sytem implemented based on employee performance appraisal in rating scale that has been standardize. Thus, company responsible at any decisions making that related to employee performace appraisal. Benchmark aspects of company performance appraisal that implemented including: honesty, hardworking, disciplines, neatness, friendliness and many more. This performance appraisal system take advantages that helps company for easier decision appraisal to employee performance with clear standard and benchmark.